Entre o real, o ficcional e o poético: de como Theodor Koch-Grünberg narrou a Amazônia - Campos, Sheila Praxedes Pereira (2012)
Above the historical knowledge, the travel narratives about Amazon also stand as imagetic forms of construction of the region in so far as these narratives are “representations” of reality seen from the subjective standpoint of foreign, relating frequently the imaginary and the symbolic. The first volume of work Vom Roraima Zum Orinoco, the German ethnographer Theodor Koch-Grünberg, is the description of his journey in the years 1911 to 1913 in the Amazon. In this report, he narrates and describes his meeting with the Indians and exuberant Amazonian nature of the circum-Roraima region. Of course this meeting with the other it could not be described from European look and, despite the scientific discourse-naturalist, and perhaps by the very force of the “new” place, Koch-Grünberg ends up doing several concessions to the poetic, constructing images to Amazon (or what he supposes as Amazon) that reveal the influence of discourses of identity (and imaginary) over/of the Amazon that circulated in Europe and revealing discursive practice that result in the conflict between plural and singular dimension. Starting from the indicting paradigm proposed by Carlo Ginzburg, this paper searches to identify some vestiges of these images captured by the German traveler, emphasizing the various ways in which he recounts an Amazon from the viewpoint on the real, fictional and poetic.